Pippi Longstocking - Lindgren, Astrid Ericsson 1907- (Scholastic, 1959)
Escapades of Pippi Longstocking, the strongest girl in the world, who lives with a horse and a monkey--but without any parents--in a villa at the edge of a Swedish village.